Optimalisasi Pemanfaatan Sumber Daya Lokal di Kabupaten Kediri - Yayuk Farida Baliwati; Khusnul Khasanah; Hidayatush Sholihin; Rahmatulloh Ramadani; Anik Dwi Oktaviani; Risaldo Ramadhan Dwi Putra; Novi Salasa; Dena Afilia Eka Candra Maulidia; Winada Almaluna; Okky Ayu Permata; Mike Tihas Nida (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
The world is currently faced with Covid-19 (Corona Virus Disease 2019) which causes many new problems in the community. Therefore, the participation of students is needed in solving these problems amid the Covid-19 pandemic which is proposed in the form of Thematic Real Work Lecture (KKN-Tematic). One of the locations chosen for the implementation of the KKN-T is Kediri Regency, East Java, which was held from July 13 to August 28, 2020. The purpose of this activity is to maintain the welfare of the community during the Covid-19 pandemic through optimizing the use of local resources. There is an increase in the existence of village social media carried out by students in an effort to develop village social media and there is also enthusiasm from the target regarding providing online marketing training for young people and village SME traders in facilitating marketing and helping increase the income of merchants affected by Covid-19. Keywords: Covid-19, Kediri, social Media, online marketing